Language Barrier and Its Impacts on Motivation and Academic Achievement among International Students at Universitas Indonesia - Jarar, Syeda Parsa; Kurniawati, Farida (Jurnal Pendidikan Humaniora, 2025)
Language barriers significantly impact the academic achievement and motivation of international students at Universitas Indonesia, where Bahasa Indonesia is the primary medium of instruction. This study explores how linguistic challenges affect students' ability to engage in coursework, participate in discussions, and integrate into academic and social life. A quantitative research approach was employed, using a Google Form-based questionnaire distributed to international students, yielding 72 responses. Descriptive statistical analysis revealed that over 90% of students faced challenges in academic writing, lecture comprehension, and subject-specific terminology, leading to reduced confidence and lower academic performance. Additionally, over 80% of students reported that language barriers affected their motivation and decisions regarding future academic opportunities. Despite the presence of language support programs, more than half of the respondents found them inadequate, highlighting a gap in institutional support. The study emphasizes the need for expanded bilingual resources, improved teaching strategies, peer mentorship, and the integration of technological tools such as AI-powered translation and subtitled lectures. Addressing these language-related challenges is crucial to enhancing student engagement, fostering academic success, and creating a more inclusive learning environment for international students.